Distinct Migration and Contact Dynamics of Resting and IL-2-Activated Human Natural Killer Cells - Olofsson, Per E.; Forslund, Elin; Vanherberghen, Bruno; Chechet, Ksenia; Mickelin, Oscar; Rivera Ahlin, Alexander; Everhorn, Tobias; Önfelt, Björn (Frontiers in Immunology, 2014)
Natural killer (NK) cells serve as one of the first lines of defense against viral infections and transformed cells. NK cell cytotoxicity is not dependent on antigen presentation by target cells, but is dependent on integration of activating and inhibitory signals triggered by receptor–ligand interactions formed at a tight intercellular contact between the NK and target cell, i.e. the immune synapse. We have studied the single-cell migration behavior and target-cell contact dynamics of resting and IL-2-activated human peripheral blood NK cells. Small populations of NK cells and target cells were confined in microwells and imaged by fluorescence microscopy for >8 h. Only the IL-2-activated population of NK cells showed efficient cytotoxicity against the human embryonic kidney (HEK) 293T target cells. We found that although the average migration speeds were comparable, activated NK cells showed significantly more dynamic migration behavior, with more frequent transitions between periods of low and high motility. Resting NK cells formed fewer and weaker contacts with target cells, which manifested as shorter conjugation times and in many cases a complete lack of post-conjugation attachment to target cells. Activated NK cells were approximately twice as big as the resting cells, displayed a more migratory phenotype, and were more likely to employ “motile scanning” of the target cell surface during conjugation. Taken together, our experiments quantify, at the single-cell level, how activation by IL-2 leads to altered NK cell cytotoxicity, migration behavior and contact dynamics.